Optimization of accelerated solvent extraction (ASE) of silver fir wood (Abies alba Mill.) - Keržič, Eli (Les (Ljubljana), 2019)
Qualitative and quantitative analysis of wood plant extractives depend on the efficiency of the extraction method used. The aim of this study was the application of the accelerated solvent extraction system ASE 350 to obtain hydrophilic extracts form silver fir wood (Abies alba Mill.) and optimization of the extraction protocol. Silver fir trees originated from Kočevska Reka. Dissected and milled samples of sapwood, heartwood and knots were extracted with the ASE 350 with water, ethanol (95 % aq), acetone (95 % aq) and ethyl acetate. The number of extraction cycles was determined. Analysis of extracts was done by UV/Vis spectrophotometry and HPLC. The most effective solvent for the extraction of phenolic components from heartwood was ethanol (95 % aq), in the case of sapwood water and acetone (95 % aq) in the case of knotwood. Only two 5-minute extraction cycles were required for sufficient extraction yield when using ASE 350 at 100 °C and 103.42 bar.
Keywords: Abies alba; accelerated solvent extraction; bela jelka; chromatography; hidrofilni ekstraktivi; hydrophilic extractives; kromatografija; les; pospešena ekstrakcija s topili; silver fir; UV/Vis; wood